2005
DOI: 10.1099/mic.0.28326-0
|View full text |Cite
|
Sign up to set email alerts
|

The putative lytic transglycosylase VirB1 from Brucella suis interacts with the type IV secretion system core components VirB8, VirB9 and VirB11

Abstract: VirB1-like proteins are believed to act as lytic transglycosylases, which facilitate the assembly of type IV secretion systems via localized lysis of the peptidoglycan. This paper presents the biochemical analysis of interactions of purified Brucella suis VirB1 with core components of the type IV secretion system. Genes encoding VirB1, VirB8, VirB9, VirB10 and VirB11 were cloned into expression vectors; the affinity-tagged proteins were purified from Escherichia coli, and analyses by gel filtration chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 65 publications
2
61
0
1
Order By: Relevance
“…VirB8 is an essential core component of all T4SSs, and previous work showed that this assembly factor undergoes multiple proteinprotein interactions (7,10,21,23,24). The x-ray structures of the periplasmic domains of both the B. suis and A. tumefaciens homologs VirB8sp and VirB8ap have been solved (25,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VirB8 is an essential core component of all T4SSs, and previous work showed that this assembly factor undergoes multiple proteinprotein interactions (7,10,21,23,24). The x-ray structures of the periplasmic domains of both the B. suis and A. tumefaciens homologs VirB8sp and VirB8ap have been solved (25,27).…”
Section: Discussionmentioning
confidence: 99%
“…VirB8 provides the structural and functional link between the cytoplasmic and inner membrane-associated energizing proteins, the other core elements, and the outer membrane-localized pilus assembly complex (7,21,22). Several interaction partners of VirB8 (VirB1, VirB4, VirB5, VirB9, VirB8, VirB10, and VirB11) have been discovered by using crosslinking, immunoelectron microscopy, and the yeast two-hybrid system (7,20,23,24). The recent finding that VirB8 nucleates T4SS assembly at the pole of A. tumefaciens emphasizes the role of its interactions (10).…”
mentioning
confidence: 99%
“…Once transported to the periplasm by the Sec secretion system, EtgA would be marginally active until it binds EscI (which is secreted through the T3SS), preventing destructive uncontrolled cell lysis. This may be a common theme for secretion system associated PG-lytic enzymes, because others such as VirB1 from the type IV secretion system have been shown to interact with components of the secretion apparatus (36).…”
Section: Tablementioning
confidence: 99%
“…Additionally, activity of specialized PG-lytic enzymes may be spatially regulated by physical interaction with other components of the molecular transport system. For instance, VirB1, a PG-lytic enzyme associated with the type IV secretion system (involved in conjugation, DNA uptake, and effector translocation), interacts with several apparatus components (36). Likewise, the interaction of EtgA with the T3SS inner rod, EscI, may spatially restrict the activity of EtgA.…”
mentioning
confidence: 99%
“…In the A. tumefaciens VirB/D4 T4S system, a disulfide bridge is formed between the reactive Cys-24 and Cys-262 residues of VirB7 and VirB9, respectively (12)(13)(14)(15). VirB9 proteins and secretins also form higher-order multimers, with themselves or with other T4S proteins, detectable by chemical cross-linking (15)(16)(17). However, secretins typically are refractory to detergent solubilization from the OM and display a heat-modifiable mobility shift in SDS-polyacrylamide gels, as is also the case for OM ␤-barrel proteins, including porins and other small molecule transporters (18).…”
mentioning
confidence: 99%